2021
DOI: 10.1002/adhm.202001896
|View full text |Cite
|
Sign up to set email alerts
|

NSCs Migration Promoted and Drug Delivered Exosomes‐Collagen Scaffold via a Bio‐Specific Peptide for One‐Step Spinal Cord Injury Repair

Abstract: Spinal cord injury (SCI) is plaguing medical professionals globally due to the complexity of injury progression. Based on tissue engineering technology,there recently emerges a promising way by integrating drugs with suitable scaffold biomaterials to mediate endogenous neural stem cells (NSCs) to achieve one-step SCI repair. Herein, exosomes extracted from human umbilical cord-derived mesenchymal stem cells (MExos) are found to promote the migration of NSCs in vitro/in vivo. Utilizing MExos as drug delivery ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 52 publications
0
52
0
Order By: Relevance
“…Natural materials can show the advantages of inherent environmental response characteristics through degradation and remodeling compared with synthetic polymers. In recent years, collagen and chitosan materials have been widely used in various tissue engineering and biomedical applications for the advantage of biodegradability, good biocompatibility, low antigenicity and absence of pyrogenic effects [ 5 , 46 , 48 , 49 ]. Collagen and chitosan were also selected as materials for 3D printing and promoting nerve regeneration after SCI in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Natural materials can show the advantages of inherent environmental response characteristics through degradation and remodeling compared with synthetic polymers. In recent years, collagen and chitosan materials have been widely used in various tissue engineering and biomedical applications for the advantage of biodegradability, good biocompatibility, low antigenicity and absence of pyrogenic effects [ 5 , 46 , 48 , 49 ]. Collagen and chitosan were also selected as materials for 3D printing and promoting nerve regeneration after SCI in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, neurons of spinal cord injury also increased at 8 days after SCI modeling ( 35 ). Moreover, endogenous neural stem cells and ependymal stem cells could differentiate into neurons after spinal cord injury ( 36 , 37 ). Lineage tracing experiments have shown that it is solely the ependymal cell population that is capable of generating neurospheres in vitro , and this hallmark of NSC potential remains restricted to the ependymal population following SCI ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of this characteristic, MExos can be used as an effective drug carrier. Researchers utilized MExos to deliver PTX via a bio-specific peptide to promote nerve regeneration and reduce scar tissue deposition, which showed excellent performance in the re-establishment of motor skills after complete SCI in rats, such that this method can repair SCI in one step (Zhang et al, 2021).…”
Section: Exosomal Mirnas Improve Sci Recoverymentioning
confidence: 99%